PUBLIC POLICY AND SUSTAINABLE INFRASTRUCTURE DEVELOPMENT - Rahmat Hidayat Djati; Liya Yulia (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2026)
Infrastructure development is a key pillar in spurring national economic growth, but large-scale projects often trigger environmental degradation and social conflict if not managed with sustainability principles. Public policy plays a crucial role as a regulatory instrument for aligning economic targets with ecological sustainability. This study aims to analyze the effectiveness of public policy in supporting sustainable infrastructure development and identify key challenges in its implementation on the ground. The research method used was descriptive qualitative, using a document study approach, examining regulations, Environmental Impact Assessment (EIA) reports, and scientific literature. The results indicate that normatively, sustainability principles have been integrated into EIA instruments. However, their effectiveness on the ground remains low due to implementation gaps. The main obstacles include overlapping cross-sectoral regulations, institutional sectoral egos, budget constraints, and minimal local community participation. This study concludes that public policy has not optimally mitigated negative environmental impacts due to weak post-permit oversight. This study recommends strengthening synergy between spatial planning regulations and simplifying green financing schemes for project implementers.